2009
DOI: 10.1103/physrevb.79.214306
|View full text |Cite
|
Sign up to set email alerts
|

Optical conductivity from local anharmonic phonons

Abstract: Recently there has been paid much attention to phenomena caused by local anharmonic vibrations of the guest ions encapsulated in polyhedral cages of materials such as pyrochlore oxides, filled skutterdites and clathrates. We theoretically investigate the optical conductivity solely due to these so-called rattling phonons in a one-dimensional anharmonic potential model. The dipole interaction of the guest ions with electric fields induces excitations expressed as transitions among vibrational states with non-eq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…In this Letter, we report the first observation of the infrared-active off-center rattling phonon in the optical conductivity of -BGS by the terahertz time-domain spectroscopy (THz-TDS), and discuss the observed results based on the AP model [19]. The observed rattling phonon spectra not only show a line splitting predicted in the model, but also reveal an unexpected, drastic linewidth broadening towards low temperature, which is quite opposite from conventional thermal behavior.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…In this Letter, we report the first observation of the infrared-active off-center rattling phonon in the optical conductivity of -BGS by the terahertz time-domain spectroscopy (THz-TDS), and discuss the observed results based on the AP model [19]. The observed rattling phonon spectra not only show a line splitting predicted in the model, but also reveal an unexpected, drastic linewidth broadening towards low temperature, which is quite opposite from conventional thermal behavior.…”
mentioning
confidence: 78%
“…For type-I Ba 8 Ga 16 Ge 30 (BGG) which shows quasi-on-center rattling of the Bað2Þ 2þ ion, the phonon dynamics have been under intense study regarding the nature of its anharmonic vibrations, e.g., far-infrared spectroscopy [16], Raman scattering [17], and inelastic neutron scattering [18]. In our previous paper [16], we reported the optical conductivity of p-type BGG and discussed the softening and sharpening of the local anharmonic phonon toward low temperature using a one-dimensional anharmonic potential (AP) model [19]. Those characteristic behaviors are explained by nonequivalent energy level spacings resultant from the flat-bottom shape of the on-center anharmonic potential, plus the Boltzmann factor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some model anharmonic potentials have been introduced to interpret experimental data on rattling Ba ion. 32 However, we have earlier found that the anharmonic potential derived from ab initio calculations is highly sensitive to details of the atomic structure. 33 As the aim of the present calculations is to aid the assignment of the experimental data we have instead applied a harmonic model also to the Ba2 atoms.…”
Section: E Theoretical Calculationsmentioning
confidence: 99%
“…Details are discussed in Ref. [10]. For the numerical calculation of σ 1 (ω, T ) for the ν 1 mode, we fix the parameters: (1/2π) k/M =1.143 THz, λ/2k × a 2 B = 0.21 (a B is Bohr radius), and the temperature-independent constant Γ 0 /2π = 0.067 THz.…”
mentioning
confidence: 99%